Bona fide praescriptio. Canon 41 Quoniam omne of the Fourth Lateran Council (1215) and Roman Law - KORPOROWICZ OPS, ŁUKASZ JAN (Prawo Kanoniczne, 2018)
According to the common opinion the canonical rule that requires good faith throughout the whole period of the prescription was introduced in can. 41 Quoniam omne of the Fourth Lateran Council in 1215. It is believed also that the rule is a denial of Roman legal maxim mala fides superveniens non nocet. It this article an author is presenting the history of the fides requirement in Roman law as well as in the canon law until the times of Quoniam omne. The analysis proves that the opinion that the bona fides rule appeared suddenly in early 13th century is false. The promulgation of the can. 41 was preceded by the long lasting tradition of the Church which implied the need of a good faith. The origins of such legal solution can be traced already in the proceedings of the ancient councils.